Subversi Salib di Papua: Semiotika Kritis Simbol Keagamaan sebagai Instrumen Perlawanan dalam Dokumenter 'Pesta Babi - Muhammad Fadli Hudayah; Muhamad Aldiansyah Saputra; Rifma Ghulam (JURNAL ILMIAH NUSANTARA, 2026)
The expansion of Indonesia’s National Strategic Project (PSN) for food and energy estates in Papua has triggered ecological crises and the dispossession of indigenous customary lands. The documentary Pesta Babi: Colonialism in Our Time (2026) captures symbolic resistance through the subversion of the Red Cross symbol. This study investigates how religious and ecological symbols are transformed into instruments of decolonial struggle and advocacy for living space. Employing a qualitative approach within a critical paradigm, Roland Barthes’ semiotic framework (denotation, connotation, myth) is combined with Liberation Theology to uncover the prophetic dimension of the oppressed’s resistance. Findings reveal that the Red Cross and the pig entity are redefined from passive objects into epicenters of collective resistance, customary boundary markers (sasi), and spiritual certificates of legitimacy that challenge state legal hegemony. In conclusion, Papuan indigenous communities liberate these symbols from institutional dogma to construct emancipatory counter-myths, where the defense of land and nature is understood as a sacred act of faith against the structural sins of capitalism.